2016
DOI: 10.1136/jim-2015-000054
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Iron Parameters and Cognitive Processes in Children and Adolescents with Dm1 Compared to those with Standard Parameters

Abstract: Anemia in patients with diabetes is not scarce and may contribute to the complications of the disease. The risk of iron deficiency parameters in child sufferers of diabetes type 1, observed in studies, can lead to cognitive impairment. The aim of the study was to determine whether children and adolescents with diabetes type 1, in whom reduced ferric parameters are observed in control tests, may also show reduced cognitive performance. The study included 100 children with diabetes type 1 at the age of 6-17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A child may develop different coping mechanisms. How they (and their loved ones) will actually cope with a disease depends on both internal resources such as personality, temperament, intelligence level, stress coping strategies, emotions, behaviour when confronted with the disease, and external resources which include support from carers, doctors, nurses and psychologists [1]. A neuropsychological assessment provides information about the level of functioning of a subject in relation to expected developmental norms.…”
Section: Introductionmentioning
confidence: 99%
“…A child may develop different coping mechanisms. How they (and their loved ones) will actually cope with a disease depends on both internal resources such as personality, temperament, intelligence level, stress coping strategies, emotions, behaviour when confronted with the disease, and external resources which include support from carers, doctors, nurses and psychologists [1]. A neuropsychological assessment provides information about the level of functioning of a subject in relation to expected developmental norms.…”
Section: Introductionmentioning
confidence: 99%
“…1 We previously reported that functional iron deficiency (ID) is common in children with T1D. 2 Since ID in children is associated with adverse effects, such as cognitive and behavioral impairment, 3,4 it is important to assess their iron status.…”
Section: Introductionmentioning
confidence: 99%